The influence of disordered eating and social media's portrayals of pregnancy on young women's attitudes toward pregnancy - A. Hope Gibson; Yuliana Zaikman (BMC, 2023)
Plain English summary Young women are more likely to have a negative body image and an unhealthy relationship with food because they are more focused on their physical appearance, especially with the rise of social media. If young women with these struggles see edited representations of pregnancy, they can develop a negative attitude about becoming pregnant in the future. This study examined how unhealthy eating habits and highly edited pictures of pregnant women impact young women's attitudes toward a potential pregnancy. Our participants answered questions designed to see if they possess unhealthy eating thoughts and behaviors, then they were randomly shown either highly edited or not highly edited pictures of pregnant women from social media. Then, they answered questions about their attitude toward a potential pregnancy. We found that women with particularly unhealthy relationships with food were less confident about maintaining healthy eating habits throughout pregnancy. However, we also found that women who viewed the highly edited pictures were more confident about maintaining healthy eating habits throughout pregnancy. We can use these results to educate caregivers and help women get better care.